2019
DOI: 10.1128/mbio.01821-19
|View full text |Cite
|
Sign up to set email alerts
|

The Ancestral N-Terminal Domain of Big Defensins Drives Bacterially Triggered Assembly into Antimicrobial Nanonets

Abstract: β-Defensins are host defense peptides controlling infections in species ranging from humans to invertebrates. However, the antimicrobial activity of most human β-defensins is impaired at physiological salt concentrations. We explored the properties of big defensins, the β-defensin ancestors, which have been conserved in a number of marine organisms, mainly mollusks. By focusing on a big defensin from oyster (Cg-BigDef1), we showed that the N-terminal domain lost during evolution toward β-defensins confers bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 53 publications
(83 reference statements)
5
63
0
Order By: Relevance
“…Basic or dibasic sites (Arg-Arg or Lys-Arg) are found between the two structural domains of big defensins. The proteolytic cleavage of the native Tt-BigDef at this dibasic site, experimentally achieved (12), generated two fragments with distinct antimicrobial activities, as also observed for the two synthetic domains of Cg-BigDef1 (21). The covalent association of Cg-BigDef1 domains is synergistic and essential for salt-stable antimicrobial activity (21).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Basic or dibasic sites (Arg-Arg or Lys-Arg) are found between the two structural domains of big defensins. The proteolytic cleavage of the native Tt-BigDef at this dibasic site, experimentally achieved (12), generated two fragments with distinct antimicrobial activities, as also observed for the two synthetic domains of Cg-BigDef1 (21). The covalent association of Cg-BigDef1 domains is synergistic and essential for salt-stable antimicrobial activity (21).…”
Section: Introductionmentioning
confidence: 62%
“…Recently, in the scallop A. purpuratus, Ap-BigDef1 was localized not only inside hemocytes but also in the digestive gland, mantle and gill tissues from challenged scallops (30). With the recent developments to produce big defensins in large amounts (21), new perspectives are now open for understanding the biology of these HDPs, from tissue distribution to function across multiple species.…”
Section: Polymorphism Of Big Defensin Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the β-defensin like C-terminal domain was not properly folded in rApBD1, we did not perform the standard antimicrobial assays used to determine the minimal inhibitory concentrations of cysteine-stabilized AMPs (Yang et al 2000;Seo et al 2005;Gueguen et al 2009). However, rApBD1 possesses an integral N-terminal domain enabling to study the potential aggregation properties of this peptide and compare them to the bacterially-triggered formation of nanonets that was described for Cg-BigDef1 (Loth et al 2019). We therefore assessed the potential formation of rApBD1 aggregates upon contact with bacteria.…”
Section: Rapbd1 Aggregates Entraps and Inhibits The Growth Of S Aureusmentioning
confidence: 99%
“…Studies related to the antimicrobial activities of big defensins have included assays testing the native polypeptide isolated from the horseshoe crab hemocytes (Saito et al 1995), recombinant polypeptide produced in bacteria (Teng, Gao and Zhang 2012) and yeast (Zhao et al 2007), and synthetic peptides obtained by chemical native ligation (Loth et al 2019). In those studies, all big defensins showed antibacterial activity against Gram-positive, Gram-negative bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%